Infant Attention and Visual Preferences: Converging Evidence From Behavior, Event-Related Potentials, and Cortical Source Localization. - Reynolds, Greg D.; Courage, Mary L.; Richards, John E. (Developmental Psychology, 2010)
In this study, we had 3 major goals. The 1st goal was to establish a link between behavioral and event-related potential (ERP) measures of infant attention and recognition memory. To assess the distribution of infant visual preferences throughout ERP testing, we designed a new experimental procedure that embeds a behavioral measure (paired comparison trials) in the modified-oddball ERP procedure. The 2nd goal was to measure infant ERPs during the paired comparison trials. Independent component analysis (ICA) was used to identify and to remove eye-movement components from the electroencephalographic data, thus allowing for the analysis of ERP components during paired comparison trials. The 3rd goal was to localize the cortical sources of infant visual preferences. Equivalent current dipole analysis was performed on the ICA components related to experimental events. Infants who demonstrated novelty preferences in paired comparison trials demonstrated greater amplitude Negative central ERP components across tasks than infants who did not demonstrate novelty preferences. Visual preference also interacted with attention and stimulus type. The cortical sources of infant visual preferences were localized to inferior and superior prefrontal cortex and to the anterior cingulate cortex. Reprinted by permission of the publisher.